"Ethical Viewing Practices": First-Graders Experiencing Racism in Let the Children March. (November 2021) - Fontanella-Nothom, Oona
Drawing upon the methodological approach of thinking with theory and the theory of the wake, this article details the process of teaching and learning about race and racism with first graders and their responses to the picturebook, Let the Children March . The theoretical concept of the weather and the corresponding theoretical strand of ethical viewing and reading practices are brought together with children's drawings and verbal responses to think with the analytical question of: what kinds of ethical viewing and reading practices can be employed and enacted with young children to engage them in racial justice and social change? The discussion and implications highlight three key insights for literacy research and practice: student agency and choice, the capability of young children, and how to approach topics of race and racism with young children with thoughtfulness. This article advances work on the teaching and learning of topics of race, racism, and antiblackness in literacy research with young people.